Multiphase Phenomena in Diesel Fuel Injection Systems - Karathanassis, Ioannis K.; Koukouvinis, Foivos (Phoevos); Gavaises, Manolis (My University, 2019)
Fuel Injection Equipment (FIE) are an integral component of modern Internal Combustion Engines (ICE), since they play a crucial role in the fuel atomization process and in the formation of a fuel/air combustible mixture, consequently affecting efficiency and pollutant formation. Advancements and improvements of FIE systems are determined by the complexity of the physical mechanisms taking place; the spatial scales are in the order of millimetres, flow may become locally highly supersonic, leading to very small temporal scales of microseconds or less. The operation of these devices is highly unsteady, involving moving geometries such as needle valves. Additionally, extreme pressure changes imply that many assumptions of traditional fluid mechanics, such as incompressibility, are no longer valid. Furthermore, the description of the fuel properties becomes an issue, since fuel databases are scarce or limited to pure components, whereas actual fuels are commonly hydrocarbon mixtures. Last but not least, complicated phenomena such as phase change or transition from subcritical to transcritical/supercritical state of matter further pose complications in the understanding of the operation of these devices.
Keywords: Multiphase flows; Diesel fuel; Injection systems; Numerical simulations; Experimental methods; Optical diagnostics; Thermodynamics